Motif Phubbing Mempengaruhi Hubungan Sosial di Kalangan Mahasiswa - Farhan Alzikri; Tessa Shasrini (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This research is entitled "Phubbing Motives Influence Social Relations Among Students". This research aims to determine the motives for phubbing influencing social relations among students at the Islamic University of Riau, Pekanbaru City, the causes of students doing phubbing. The method used in this research is a qualitative method with a descriptive approach. The subjects in this research were teenagers who carried out phubbing in the Riau Islamic University campus area. In the research there were 5 teenagers who carried out phubbing who became informants. The results of this research show that there are 2 motives for phubbing, the first is because of motive, namely a feeling of not being appreciated, boredom, and uncomfortable. The second in order motive is to entertain oneself, obtain information, social needs. In this activity there are causes for phubbing, namely reflex actions and following people around.